Przechwycić traumę, czyli Aleksandra Petrova opowieść o serbskim cierpieniu (Politeja, 2023)
TO SEIZE THE TRAUMA: ALEKSANDAR PETROV’S STORY ABOUT THE SERBIAN SUFFERINGThe paper focuses on Aleksandar Petrov’s novel Kao zlato u vatri, originally published by this Serbian author in 1998. The novel’s main characters represent diverse ethnic groups inhabiting the Balkans ( Jews, Serbians, Russians), and their fortunes intertwined with the tumultuous events of 20th century history, namely WWII and the Yugoslav Wars of the 1990s. The primary objective of the article is to address the question of whether it is feasible to apply Michael Rothberg’s model of multifaceted memory in a scenario involving distinct memory communities (such as Serbs, Croatians, and possibly Jews), characterized by a specific proximity (primarily territorial, historical and rooted in past coexistence within one national entity) and where relations are predominantly shaped by unresolved past grievances and mutual accusations of guilt.